Reproductive performance of beef heifers following timed-artificial insemination: the role of temperament and acclimation to human handling and the handling facility - Tastad, Sydney Hilde (My University, 2025)
A goal of beef cattle production is for each cow to produce one calf per year. This standard is vital for the efficiency of cow-calf operations. Achieving this goal requires strategic management of heifer development to optimize reproductive success in their first year. The success or failure of a heifer to become pregnant early in her first breeding season affects her performance in the subsequent year. Furthermore, heifers that calve early in their first calving season stay in the herd longer and wean heavier calves than those that calve later. The timing of a heifer’s first parturition can influence her productivity for up to the next 6 calving seasons, ultimately impacting her ability to produce one calf per year. Therefore, becoming pregnant early in her first breeding season is of great importance. An effective management strategy to increase the number of heifers that become pregnant early in the breeding season is to implement an estrus synchronization (ES) protocol and timed artificial insemination (TAI). However, the success of ES and TAI can be influenced by many factors, including heifer temperament. Previous studies have demonstrated that heifers with excitable temperaments have greater plasma cortisol concentrations and decreased conception rates to TAI compared with calm heifers. However, plasma cortisol concentrations decrease as the handling events of an ES protocol progress. Moreover, acclimation to human handling and the facility has been shown to improve reproductive outcomes following ES and TAI in cows and natural service breeding in heifers. The objectives of this study were to investigate the effects of acclimating heifers to the human handling and the facility during the handling events of an ES protocol on temperament and conception rates to TAI. We hypothesized that acclimating heifers to human handling and the facility during the handling events of the ES protocol would improve temperament and lower plasma cortisol concentrations by TAI, and acclimated heifers would have greater conception rates to TAI than non-acclimated heifers. Before enrollment in the study, 622 Bos taurus yearling commercial beef heifers from five herds in the spring of 2023 and three herds in the spring of 2024 (reported as 8 locations in total) were evaluated for reproductive tract score (RTS), chute score (CS), and exit velocity (EV). Heifers at each location were stratified based on CS and RTS to be acclimated to human handling and the facility during the handling events of the ES (TRT; n = 307) or serve as control (CTRL; n = 315). They were tagged according to treatment and managed as one group at each location. All heifers were enrolled in the 7-day CO-Synch + CIDR ES protocol and received TAI. The CIDR was inserted on d 0 of the study, removed on d 7, and TAI occurred on d 10. Before the ES protocol handling events (d 0, 7, and 10), TRT heifers were sorted off and acclimated to the handling facility by moving them through the tub, ally, and chute without restraint. After acclimation, they were commingled with CTRL heifers and returned to the facility for the ES event of that day. To assess temperament, CS and EV were collected for all heifers on d 0, 7, and 10 of the study. Additionally, blood samples were collected for 120 heifers from 2 locations, to analyze plasma cortisol concentrations (d 0, 7, 10). Estrus detection patches were placed on d 7 and scored on d 10. Pregnancy status was determined between 40 days and 91 days post-TAI by transrectal ultrasonography. No treatment effects were observed for RTS (P = 0.78), CS (P = 0.99), or EV (P = 0.87) on d -10. Exit velocities decreased as the protocol progressed for all heifers (P < 0.0001) but did not differ based on treatment (P = 0.27). Additionally, no differences were observed for estrus patch scores (P = 0.46) between treatments. There were no differences in cortisol concentrations between TRT and CTRL heifers (P = 0.64). However, TRT heifers had decreased CS on d 7 (P = 0.01) and d 10 (P = 0.01) when compared to CTRL, and greater conception rates to TAI (54% for TRT and 45% for CTRL; P = 0.02). These results suggest that acclimating heifers to human handling and the facility during the handling events of the 7-day CO-Synch + CIDR ES protocol led to improved chute scores, indicating a potential improvement in temperament, and effectively improved conception rates to TAI.
Keywords: Beef heifer; Reproduction; Acclimation; Temperament